Long-term outcomes in patients with potential reversible causes of bradycardia. (19th May 2022) - Passos, M; Fialho, I; Lopes, J; Mateus, C; Beringuilho, M; Baltazar, J; Santos, M; Augusto, J
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: Hyperkalemia and negative chronotropic drugs are well known causes of reversible bradycardia. Their synergic combination may result in BRASH syndrome (Bradycardia, Renal failure, Atrioventricular blockade, Shock, and Hyperkalemia), a consequence of the vicious cycle between bradycardia, renal failure and worsening hyperkalemia, leading ultimately to multiorgan dysfunction. In potentially reversible bradycardia, drug discontinuation or metabolic correction is recommended before permanent pacemaker (PPM) implantation. Objectives: To determine the long-term prognosis in patients with potentially reversible symptomatic bradycardia. Methods: We retrospectively reviewed 176 patients who presented to the emergency department with symptomatic bradycardia, between January 2015 and August 2016. Patients without any reversible cause of bradycardia were excluded. Participants were stratified into three groups according to the reversible causes of bradycardia: patients with hyperkalemia, with or without acute renal injury (ARI) (group 1); patients taking negative chronotropic drugs, with or without ARI (group 2); patients with BRASH syndrome (combination of hyperkalemia and negative chronotropic drugs, with or without ARI) (group 3). The primary endpoint was PPM implantation after discharge. Secondary endpoints included: bradycardia-related rehospitalization, heart failure (HF) hospitalization, all-cause mortality and a composite of all the previous endpoints. Results: A total of 105 patients were included (52.4% female; mean age 79.8±8.6 years). Group 1 was comprised by 15 patients (14.3%), group 2 by 69 patients (65.7%) and group 3 by 21 patients (20%, figure 1). The incidence of each event is presented in figure 2. During a mean follow-up of 3.2±2.1 years, PPM was implanted in 60 patients (57.1%) – 51 during hospital stay (85%) and 9 after discharge (15%). Across all groups, approximately 50% of the patients needed PPM implantation at some point, without significant differences between groups (p=0.508). Group 3 had the lowest need of in-hospital PPM (38.1%) but the highest bradycardia-related readmissions (9.5%). Nevertheless, post-discharge PPM implantation was still higher in group 1 (33.3%), followed by group 3 (22.2%). There were no significant differences in the post-discharge PPM implantation rate between groups (p=0.76). In groups 1 and 3 the composite endpoint (73.3% and 76.2%, respectively) was significantly more frequent than in group 2 (44.9%, p=0.046 and p=0.012, respectively). Conclusions: Nearly half of the patients with an episode of reversible bradycardia needed a PPM at some point. Given the advanced age of most patients with bradycardia secondary to metabolic derangement and/or drug toxicity, it is possible that this unveils underlying conduction system disease, which is likely to recur without PPM implantation.